(3eHGOF GdJMdjd Gdcej (B/s - (3CHh HcQ, YjO CMeOs; (3GdSjah, hdjO GSeGYjd s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2009)
(3GdJMdjd Gdcej ddYdGbI Hjf GdfJZjQGJ GdGbJUGOjI , (B: (3JMdjd GdJYGOd , GdOGdI GdJQHjYjI , GdGeKdjI ddOhGd GdGbJUGOjI , GdeMOOGJ (B: (3WHjYIh GSJNOGeGJ h NUGFU GdeMOOGJ , GSJNOGe GdeMOOGJ aj Md GdeTGcd GdGbJUGOjI h GdGOGQjI h GdeGdjI , GdeUahaGJ (B: (3WHjYI GdeUahaGJ h GdYedjGJ GdLHQjI YdjgG, GSJNOGe GdeUahaGJ aj Md GdeTGcd GdSGHbI , CSdhH GdHQeLI GdNWjI (B: (3WHjYI GdHQeLI GdNWjI ,GSJNOGe GdWQjbI GdHjGfjI h WQjbI GdSeHdcS aj Md feGPL GdHQeLI GdNWjI , GdeTcdI GdebGHdI (B.s
(3eQGLY U(B.311s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEbJUGO GdbjGSjs; (3GdHQeLjGJs; (3GdJMdjd GdEMUGFjs; (3GdMGShHs